2018
DOI: 10.3904/kjm.2018.93.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Diastolic Function on Clinical Outcomes in Young Patients with Acute Myocardial Infarction

Abstract: Background/Aims: The impact of left ventricular (LV) diastolic function and filling pressure on clinical outcomes in young patients with acute myocardial infarction (AMI) has been poorly studied. Therefore, the aim of this study was to investigate the impact of LV diastolic function and LV filling pressure on major adverse cardiac events (MACEs) in young patients with AMI. Methods: A total of 200 young patients (males < 45 year, females < 55 year) with AMI were divided into two groups according to the diastoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 7 Several diastolic function parameters that were introduced and used for predicting the clinical outcome in acute MI include the LV filling pattern, deceleration time, LA volume index, Tei index, and E/e’ ratio. 12 , 19 , 20 According to the latest recommendations, the E/e’ ratio and mitral annular early diastolic velocity (e’) using pulse-wave Doppler are strongly recommended for the assessment of LV diastolic dysfunction. 21 The early mitral inflow velocity increases while e’ decreases under elevated LV filling pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Several diastolic function parameters that were introduced and used for predicting the clinical outcome in acute MI include the LV filling pattern, deceleration time, LA volume index, Tei index, and E/e’ ratio. 12 , 19 , 20 According to the latest recommendations, the E/e’ ratio and mitral annular early diastolic velocity (e’) using pulse-wave Doppler are strongly recommended for the assessment of LV diastolic dysfunction. 21 The early mitral inflow velocity increases while e’ decreases under elevated LV filling pressure.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Among the established prognostic factors, several studies have demonstrated the ascendancy of the E/e’ ratio over other variables. 6 , 20 , 25 However, these studies were conducted in patients with acute MI, in which reperfusion therapy timing was different. To reduce such bias, we only included patients with STEMI who underwent coronary intervention within 12 hours of hospital arrival.…”
Section: Discussionmentioning
confidence: 99%